Approaches to offender rehabilitation in Asian jurisdictions - Chu, Chi Meng; Daffern, Michael (International perspectives on forensic mental health, 2024)
"This book aims to understand how Asian jurisdictions conceptualise rehabilitation within both the correctional and forensic mental health sectors. Little has been written about rehabilitation practices for people in criminal justice and forensic mental health services in Asia. Although there is some recognition of the need to develop and/or adjust rehabilitation practices for non-white/non-western peoples in Western jurisdictions, the extent to which Western-derived practices have been considered, adjusted, or adopted in Asian countries is not well known. This book includes contributions from an international team to explore the ways in which history, culture, religion, and resources impact how rehabilitation is conceptualised and offered in multiple Asian countries. It aims to provide an understanding of the relative merits of contemporary Western practices across different Asian countries and consider how these practices have been adopted within correctional and forensic mental health sectors. This book is essential for administrators who are developing rehabilitation strategies and for practitioners working with people who have a history of offending behaviour"--